Pengembangan e-Modul Berbasis STREAM Materi Kubus dan Balok Untuk Meningkatkan Hasil Belajar di MI Nor Rahman Banjarmasin - Annisa Sholehati; Wahyu Hengky Irawan; Abdussakir (Institut Agama Islam Negeri Palangka Raya, 2025)
This study was conducted based on the need for an electronic teaching module that can be used by students independently. Able to integrate Islamic values in mathematics learning in class V MI Nor Rahman on the material of cube and cuboid shapes. This study aims to develop and determine the level of feasibility and effectiveness of STREAM-based mathematics learning e-modules on cube and cuboid material for class V MI Nor Rahman Banjarmasin students. The e-Module developed is based on STREAM (Science, Technology, Religious, Engineering, Art, and Mathematics). Integrating STEAM and religious values to improve learning outcomes.This study uses the ADDIE development model(Analyze, Design, Develop, Implement, Evaluate). Data collection techniques using observation, interviews, questionnaires, tests, and documentation with qualitative and quantitative data analysis techniques.The results of the e-module development show validity. The results of the media expert validation with an average value of 76.8%, the material expert obtained a value of 78.6%, the language expert showed a value of 72%, the validation of Islamic education experts obtained a value of 90%, the validation of learning experts obtained a value of 90.5%. While the validation of learning practitioners (mathematics teachers) obtained an average value of 88.3%, which strengthens the finding that this e-module is very practical and feasible. The attractiveness data shows a percentage of 86.18%, which is categorized as very interesting. The results of the effectiveness of media use show that the average results in the experimental class have increased, namely from the pretest 58, increasing in the posttest to 85. The results of the t-test show a significance value (2-tailed) of 0.000 which is smaller than 0.05. This shows a significant difference between student learning outcomes in the experimental class and the control class.